2021
DOI: 10.1007/s12291-021-00967-0
|View full text |Cite|
|
Sign up to set email alerts
|

“Silent Hypoxemia” Leads to Vicious Cycle of Infection, Coagulopathy and Cytokine Storm in COVID-19: Can Prophylactic Oxygen Therapy Prevent It?

Abstract: Humankind is facing its worst pandemic of the twenty-first century, due to infection of a novel coronavirus named as SARS-CoV2, started from Wuhan in China. Till now, 15 million people are infected, causing more than 600,000 deaths. The disease, commonly known as, COVID-19, was initially thought to be associated with ARDS only, but later on revealed to have many unexplained and atypical clinical features like coagulopathy and cytokinemia, leading to multi-organ involvements. The patients also suffer from ‘ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…One of the main reasons for the development of SI and mortality in COVID-19 is hypoxemia linked with respiratory failure and systemic tissue hypoxia associated with several causes of impaired oxygen transport [ 63 , 64 , 65 , 66 ].…”
Section: Systemic Reactions In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the main reasons for the development of SI and mortality in COVID-19 is hypoxemia linked with respiratory failure and systemic tissue hypoxia associated with several causes of impaired oxygen transport [ 63 , 64 , 65 , 66 ].…”
Section: Systemic Reactions In Covid-19mentioning
confidence: 99%
“…Similarly, hypoxemia/hypoxia is thought to be an independent risk factor for hospital mortality in the most critical forms of ARDS [ 63 , 64 , 65 , 66 ], as it is linked to the development of multiple organ failure and coagulopathy [ 63 , 64 , 65 , 66 ]. COVID-19 patients frequently develop hypoxemia without signs of breathlessness though their chest X-rays show diffuse pneumonia, and dangerous levels of blood oxygen are detected [ 63 ]. Meanwhile, low saturation values cause cascades of molecular changes in many tissues, which can trigger a chain of events that result in organ damage that can be fatal [ 63 ].…”
Section: Systemic Reactions In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that hypoxia induces Early Growth Response 1, which in turn regulate thrombus formation [137,138]. Moreover, HIFs or HIF targeted genes induces prothrombotic factors like PAI-1 and tissue factors, while antithrombotic factors like thrombomodulin, Protein S and TFPI [139][140][141][142][143]. However, the exact role of these pathways is yet to be elucidated in COVID-19 pathology.…”
Section: Involvement In Immunity and Sars-cov-2 Infectionmentioning
confidence: 99%
“…However, low levels of oxygen lead to damage in several tissues and it has been suggested that this can increase infection by up regulation of furin (via HIF-1α), a host enzyme required for cleaving the S protein of the SARS-CoV2 [ 27 , 28 ]. Hypoxemia has also been related to proinflammatory cytokines [ 29 ].…”
Section: Introductionmentioning
confidence: 99%